Comparing monotherapy with tadalafil or tamsulosin in men with benign prostatic hyperplasia: A case-control study - Hayder Adnan Fawzi; Saif Nabeel Akram; Aya Fawzi Talib; Mustafa Hasan Alwan; Luma Amer Yasir (Wolters Kluwer Medknow Publications, 2024)
Benign prostatic hyperplasia (BPH) is a chronic disorder that inflicts severe symptoms on middle-aged men. The current study compared the effects of tadalafil and tamsulosin on urological parameters after 3 and 6 months of therapy. A retrospective case-control study was conducted, in which 100 patients with moderately severe BPH were divided into two groups based on their treatment: 50 patients were given tamsulosin 0.4 mg/day and group 50 patients were administered tadalafil 5 mg daily. All patients continued therapy for approximately 6 months, and their urological parameters were assessed at baseline and after 3 and 6 months. There was no significant difference in the overall effect on the International Prostate Symptom Score at the end of the study using two-way ANOVA analysis (P = 0.448). The intercourse number was significantly improved by tadalafil compared to tamsulosin (P < 0.001). The prostatic-specific antigen, postvoiding residual, and prostatic volumes were not significantly different between tadalafil and tamsulosin (P = 0.198, 0.163, and 0.183, respectively). In conclusion, tadalafil, 5 mg once daily, appears to have similar efficacy to tamsulosin, with significant improvement in the patient's erectile function. Tadalafil can be used for 6 months for moderate-to-severe lower urinary tract symptoms.